2022
DOI: 10.3390/ma16010176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Cylindrical Vector Beams for Improved Energy Feedthrough and Low Roughness Surface Ablation of Metals

Abstract: The use of ultrafast cylindrical vector vortex beams in laser–matter interactions permits new ablation features to be harnessed from inhomogeneous distributions of polarization and beam geometry. As a consequence, the ablation process can yield higher ablation efficiency compared with conventional Gaussian beams. These beams prevent surface quality degradation during the ablative processes. When processing stainless steel and titanium, the average surface roughness obtained by deploying the cylindrical vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the axis-centered circles in the focal plane for which |T(r)| > |R(r)|, the spin density S z is positive and, vice versa, on circles where |T(r)| < |R(r)|, the spin density is negative. Thus, we have shown that at the tight focus of field (21), the sign of the longitudinal spin component S z is alternating. Assuming a positive S z on some radius in the focal plane, we find that with increasing radius, S z is decreasing before becoming zero and then negative with further increasing radius.…”
Section: An Azimuthally Polarized Optical Vortexmentioning
confidence: 69%
See 4 more Smart Citations
“…On the axis-centered circles in the focal plane for which |T(r)| > |R(r)|, the spin density S z is positive and, vice versa, on circles where |T(r)| < |R(r)|, the spin density is negative. Thus, we have shown that at the tight focus of field (21), the sign of the longitudinal spin component S z is alternating. Assuming a positive S z on some radius in the focal plane, we find that with increasing radius, S z is decreasing before becoming zero and then negative with further increasing radius.…”
Section: An Azimuthally Polarized Optical Vortexmentioning
confidence: 69%
“…the optical axis, the major axis vector of the polarization ellipse in Figure 3 makes four half-turns, or two full turns. When compared to the polarization singularity index for V-point in the original plane (η = 1), a larger singularity index value at the focus for the C-point (IC = 2) is due to the fact that while in the original plane, the optical vortex topological charge (n = 1) has no effect on the singularity index of field (21), in the focal plane, the optical vortex changes the polarization pattern topology, increasing the polarization index value by 1 thanks to extra phase jumps by π.…”
Section: Numerical Modelingmentioning
confidence: 98%
See 3 more Smart Citations